Recombinant junctions formed by site-specific integration of adeno-associated virus into an episome. - Giraud, C (1995)
A model system using an episomal Epstein-Barr virus shuttle vector was recently developed to study the adeno-associated virus (AAV) site-specific integration event in chromosome 19q13.3-qter (C. Giraud, E. Winocour, and K.I. Berns, Proc. Natl. Acad. Sci. USA 91:10039-10043, 1994). In this study, we analyze the recombinant junctions generated after integration of the AAV genome into an Epstein-Barr virus shuttle vector carrying 8.2, 1.6, or 0.51 kb of the chromosome 19 preintegration sequence (AAVS1 locus). In most of the recombinants, one end of the viral genome was joined to a portion of the AAVS1 DNA previously shown to be a minimum target for AAV integration. Within this AAVS1 segment, the AAV insertion points were strikingly clustered around a binding site for the AAV regulatory protein. In all cases, the second junction with AAV occurred with vector DNA outside of the AAVS1 segment. With respect to the viral genome, one junction with the shuttle vector DNA occurred either within the AAV inverted terminal repeat (itr), or near the P5 promoter, approximately 100 nucleotides distal to a modified itr. The modified itr in 5 of 11 recombinants involved a head-to-tail organization. In one such instance, the AAV insert contained slightly more than one genome equivalent arranged in a head-to-tail manner with a junction close to the P5 promoter; the AAV insert in this recombinant episome could be rescued by adenovirus infection and replicated to virus particles. The significance of the head-to-tail organization is discussed in terms of the possible circularization of AAV DNA before or during integration.